Study of Crude oil spills and gas burning of accompanied natural gas on the environment of Nasiriyah oil field southern Iraq - عريبي الدخيلي محسن; هديرس نعيثل عيسى (University of Thi-Qar Journal of Science, 2016)
The” current study involves the use of The device utilizes to measure concentration, and identification of origin, and distribution of Polycyclic Aromatic Hydrocarbons in the soil, depths of laminar water well column, and groundwater by high performance liquid chromatography device which contains at high precision separation techniques, within the Nasiriyah oilfield, for the period of October2015 until September 2016. This study is based on the compounds of Polycyclic Aromatic Hydrocarbons which can penetrate from surface soil into groundwater across different layers. Moreover, it depends on following the change in concentrations of these compounds and its associated elements are used as a means to track the descent of these materials into the groundwater. The change in concentrations which were taken at different distances (0,35,70,210,420,630) meters from the "source of contamination, the concentrations of Polycyclic Aromatic Hydrocarbons(PAHs) in the soil ranged between (0.003) µg/Kg at station six PS6 and (73.462) µg/Kg at station one PS1, In addition, there are another samples were taken at different depths, such as (10, 20, 30, 40, 50, 60) meters along the well column ranged between(0.303) µg/Kg When depth 50 meters and(1.072) µg/Kg When the soil surface, and this was a way to find a type of comparison between the change of concentration and distance. The “compounds’ source of PAHs into the soil and groundwater is common between Pyrogenic and Petrogenic. Thisfact is because of two reasons.